The Bible in American Poetic Culture Community, Conflict, War - Wolosky, Shira (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
Although the Bible is the foundation of American poetic tradition, there is no study of the Bible as an ongoing force in American poetry. Not only a source of imagery, allusion, rhythm and style, the Bible is central to how poetry has both shaped and been shaped by American civic, political, and social history, including issues of ethnicity, race and gender. Through poetry core issues of the Bible in American culture emerge in a new light. What defines America as a nation? What are its historical, political and religious meanings and direction? Vitally, how is it that the Bible is at once a shared common text, binding community, and yet was throughout American culture also contested, disputed, and politicized as a weapon of war? This study begins with the Puritans, and goes on to examine poetry of the Revolutionary and Civil Wars, as well as claims and counterclaims in abolition, slavery, and women's rights. In doing so it treats both popular and major writers, including Edward Taylor, Frances Harper, Emerson, Whitman, Dickinson, Moore and Gwendoln Brooks, concluding with Amanda Gorman. Shira Wolosky is Professor of English and American Studies at the Hebrew University of Jerusalem, Israel. Previous publications include Emily Dickinson: A Voice of War (1984), Poetry and Public Discourse in Nineteenth Century America (2010), and Feminist Theory across Disciplines: Feminist Community and American Women's Poetry (2013). Her awards and research appointments include a Fulbright Fellowship, a Whiting Fellowship, a Guggenheim Fellowship, Fellowships at the Institute of Advanced Studies, Princeton, a Tikvah Fellowship at NYU Law School, and Drue Heinz Visiting Professorships at Oxford.
1. The Bible as Public Sphere: Interpretation, Polity, Poetry -- 2. Puritan Hebraism: John Cotton and Edward Taylor -- 3. Covenant and Apocalypse: Revolutionary and Civil Wars -- 4. The Bible Divided Against Itself: Abolition, Slave Spirituals -- 5. Rewriting Scripture: Emerson, Whitman, Melville -- 6. Emily Dickinson's Biblical Contests: Critique, Gender, War -- 7. Women's Bibles, White and Black.
Keywords: Poetry; Bible -- Study and teaching; America -- Literatures; Ethnology -- America; Culture; Poetry and Poetics; Biblical Studies; North American Literature; American Culture